PEMBUATAN TEH KOMBUCHA BERBAHAN DASAR TEH HIJAU - Chahya, Anisha; Dartiani Sagurung, Mariance; Situmorang, Rivaldo; Advinda, Linda (Universitas Cokroaminoto Palopo, 2025)
Kombucha tea is a very interesting traditional drink because this tea is the result of fermentation carried out by a symbiotic culture. The symbiotic culture is SCOOBY (Symbiotic Culture Of Bacteria And Yeast). The tea that can be used is green tea. Green tea contains compounds such as tannins, caffeine, flavonols, flavonoids, alkaloids and saponins. Different types of tea can affect the color of the kombucha. The fermentation time for kombucha tea is 7-14 days. Fermentation time can affect the degree of acidity and physical properties of kombucha tea. This research is a descriptive study which aims to determine the pH and organoleptic properties, namely taste, aroma, color and how to make kombucha tea. The research results showed that the pH of kombucha tea was 2 and in the organoleptic test, many panelists preferred green tea kombucha.